Occupational Road Safety 2020: Using PESTELED Analysis to Understand the Work-Related Road Safety Context - Will Murray (Journal of Road Safety, 2011)
Since the formation of the coalition government in the UK there has been increasing focus on, and debate about, cuts in the road safety budget. Such cuts will have many knock-on effects for road safety, including the work-related or fleet sector. This means that it is increasingly important for all sectors of the fleet industry, and its suppliers, to fully understand the external context in which they find themselves, particularly when trying to make long term plans. Work-related road safety is influenced by external economic, legal and political factors which operate at local, national and international levels. These factors influence organisational changes such as management structures, which in turn influence work context and job characteristics at organisational and individual levels. When developing a work-related road safety program - for all vehicle types from heavy trucks and buses, right down to couriers on two wheeled machines - it is vital to understand and allow for such external factors. During the 1980s, a PEST (political, economic, social and technological) analysis was developed as the way to do this. Then in the 1990s, this concept expanded into a PESTEL (political, economic, social, technological, environmental and legal) analysis. Now the tool has further evolved into a PESTELED (political, economic, social, technological, environmental, legal, ethical and demographic) analysis.